Upper-plate conduits linked to plate boundary that hosts slow earthquakes - Ryuta Arai; Seiichi Miura; Yasuyuki Nakamura; Gou Fujie; Shuichi Kodaira; Yuka Kaiho; Kimihiro Mochizuki; Rie Nakata; Masataka Kinoshita; Yoshitaka Hashimoto; Yohei Hamada; Kyoko Okino (Nature Communications, 2023)
Abstract In shallow subduction zones, fluid behavior impacts various geodynamic processes capable of regulating slip behaviors and forming mud volcanoes. However, evidence of structures that control the fluid transfer within an overriding plate is limited and the physical properties at the source faults of slow earthquakes are poorly understood. Here we present high-resolution seismic velocity models and reflection images of the Hyuga-nada area, Japan, where the Kyushu-Palau ridge subducts. We image distinct kilometer-wide columns in the upper plate with reduced velocities that extend vertically from the seafloor down to 10–13 km depth. We interpret the low-velocity columns as damaged zones caused by seamount subduction and suggest that they serve as conduits, facilitating vertical fluid migration from the plate boundary. The lateral variation in upper-plate velocity and seismic reflectivity along the plate boundary correlates with the distribution of slow earthquakes, indicating that the upper-plate drainage system controls the complex pattern of seismic slip at subduction faults.